Language-Related Communication Stress Among Yemeni Student Diaspora in Karnataka, India - Musleh AL-Badaji, Siham; Varghese , P.A. (International Journal of Social Sciences and Management, 2022)
Foreign students, who get admission to various universities and educational institutions in various countries, undergo immense stress and struggles due to socio-linguistic and cultural barriers. Though this get diluted in the long-run, the problems can be easily minimized. The present study looks in to the problems faced by Yemeni student diaspora in India, and as a case study in Karnataka, a southern state. The personal life, social life and especially the student life is studied based on their reactions to various statements on stress. The study found that Yemeni students undergo tremendous pressures and stress as a foreign student, due to lack of language skills, special accents, and use of native language by people they interact. The researcher suggests training in linguistic skills, openness and hard work as solutions. Int. J. Soc. Sc. Manage. Vol. 9, Issue-2: 83-87.